Environmental measurements from the Ebro Delta coastal area during MERS-BLUEISLAND cruise (November 2019) - Marina Addante; Michaël Grelaud; Gerald Langer; Patrizia Maiorano; Sergio Bonomo; Marta Álvarez; Roberta Johnson; Patrizia Ziveri (PANGAEA, 2024)
The present dataset contains environmental variables: temperature, salinity, fluorescence, turbidity, nitrite, nitrate, phosphate, silicon dioxide, total alkalinity, dissolved inorganic carbon and pH. The samples were collected between Barcelona and the Ebro Delta (Western Mediterranean), during the MERS-BLUEISLAND cruise in November 2019, with rosette Niskin bottles equipped with CTD investigating the photic zone (0-200 m).